THE EFFECT OF FUNDING POLICY, DIVIDEND POLICY, COMPANY SIZE AND PROFITABILITY ON COMPANY VALUE IN MANUFACTURING COMPANIES - Yanuarini, Lily; Iramani, Rr. (JURNAL EKBIS, 2023)
The aim of this research is to examine and analyze the effect of funding policy, dividend policy, profitability and firm size simultaneously and partially on firm value. This study uses causal research. The data source for this research is secondary research. The sampling technique in this study was to use purposive sampling method. The research population is a manufacturing company listed on the Indonesia Stock Exchange. The type of data used is secondary data sourced from the publication of annual reports obtained from www.idx.co.id and the Indonesian Capital Market Directory. The analysis technique uses Multiple Regression Analysis (MRA). The results of the study show that funding policies, dividend policies, profitability and firm size simultaneously affect firm value. And funding policies, dividend policies, profitability and firm size partially affect firm value. Future researchers are expected to be able to take other variables that can affect company value.